PERANCANGAN SINGLE AXIS TRACKING SYSTEM - Arifin, Yusnaini; Magga, Ramang; Hatib, Rustan (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2013)
The aim of this research is to track photovoltaic panel following sun orientation in order to obtain maximum output of the panel. This research has been conducted in mechanical and electrical laboratory. The tracking system has used dc motor that utilizes AT Mega 8535 microcontroller to control the movement of the tracking system. The movement is 15o every hour, from east to west (8 pm – 4 am). Keywords: photovoltaic, single axis, tracking system.